1998
DOI: 10.1074/jbc.273.14.8193
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Human GDP-mannose 4,6-Dehydratase and Reconstitution of GDP-fucose Biosynthesis in Vitro

Abstract: We have cloned the cDNA encoding human GDP-mannose 4,6-dehydratase, the first enzyme in the pathway converting GDP-mannose to GDP-fucose. The message is expressed in all tissues and cell lines examined, and the cDNA complements Lec13, a Chinese Hamster Ovary cell line deficient in GDP-mannose 4,6-dehydratase activity. The human GDP-mannose 4,6-dehydratase polypeptide shares 61% identity with the enzyme from Escherichia coli, suggesting broad evolutionary conservation. Purified recombinant enzyme utilizes NADP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 32 publications
7
128
1
Order By: Relevance
“…The virus GMER behaves as a bifunctional enzyme, with an epimerization activity that leads to a change in the sugar configuration, followed by the NADPHdependent reduction of the 4-keto group of the intermediate to form GDP-L-fucose. These GMD and GMER activities are identical to those of GMD and GMER enzymes from prokaryotes, plants, and animals (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The virus GMER behaves as a bifunctional enzyme, with an epimerization activity that leads to a change in the sugar configuration, followed by the NADPHdependent reduction of the 4-keto group of the intermediate to form GDP-L-fucose. These GMD and GMER activities are identical to those of GMD and GMER enzymes from prokaryotes, plants, and animals (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 55%
“…In the present study we characterize two PBCV-1 ORFs, A118R and A295L, that encode proteins that resemble GDP-D-mannose 4,6-dehydratase (GMD) and GDP-4-keto-6-deoxy-D-mannose epimerase/reductase (GMER), respectively. GMD and GMER are highly conserved proteins involved in GDP-L-fucose formation in bacteria, plants, and animals (11)(12)(13)(14)(15). Enzyme analyses, performed on both the recombinant proteins and extracts from PBCV-1-infected Chlorella cells, indicate that both proteins are functionally active, leading to the production of two nucleotide sugars, GDP-Lfucose and GDP-D-rhamnose.…”
Section: Paramecium Bursaria Chlorella Virus (Pbcv-1)mentioning
confidence: 99%
“…The GDP-L-fucose product is the donor carbohydrate utilized by a variety of fucosyl-transferases that add it to various lactosamine acceptors, decorating both glycoproteins and glycolipids (33,34). Results by Ohyama et al (34) suggested that the transcription of FX and possibly also GDP-mannose 4,6-dehydratase is regulated by metabolites generated in the fucose synthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis of GDP-L-fucose is mediated by mannose 4,6-dehydratase, 3,5 epimerase and 4-ketoreductase activity in both eukaryotic and prokaryotic organism. 44,45 Accordingly, Ata12 (mannose 4,6-dehydratase) and Ata17 (epimerase/dehydratase) may be involved in the synthesis of GDP-D-mannose. Furthermore, the unsaturated hexofuranose moiety could be synthesized from GDP-D-rhamnose through Ata10 (oxidoreductase), and Ata13 (mannosyltransferase) could link it to that D-rhamnose.…”
Section: A201a Antibiotic Biosynthetic Gene Cluster (Ata) I Saugar Et Almentioning
confidence: 99%